MicroRNA-1 regulates chondrocyte phenotype by repressing histone deacetylase 4 during growth plate development - Li, Pengcui (Federation of American Societies for Experimental Biology, 2014)
MicroRNAs (miRs) are noncoding RNAs (17–25 nt) that control translation and/or mRNA degradation. Using Northern blot analysis, we identified that miR-1 is specifically expressed in growth plate cartilage in addition to muscle tissue, but not in brain, intestine, liver, or lung. We obtained the first evidence that miR-1 is highly expressed in the hypertrophic zone of the growth plate, with an 8-fold increase compared with the proliferation zone; this location coincides with the Ihh and Col X expression regions in vivo. MiR-1 significantly induces chondrocyte proliferation and differentiation. We further identified histone deacetylase 4 (HDAC4) as a target of miR-1. HDAC4 negatively regulates chondrocyte hypertrophy by inhibiting Runx2, a critical transcription factor for chondrocyte hypertrophy. MiR-1 inhibits both endogenous HDAC4 protein by 2.2-fold and the activity of a reporter gene bearing the 3′-untranslated region (UTR) of HDAC4 by 3.3-fold. Conversely, knockdown of endogenous miR-1 relieves the repression of HDAC4. Deletion of the miR-1 binding site in HDAC4 3′-UTR or mutated miR-1 abolishes miR-1-mediated inhibition of the reporter gene activity. Overexpression of HDAC4 reverses miR-1 induction of chondrocyte differentiation markers Col X and Ihh. HDAC4 inhibits Runx2 promoter activity in a dosage-dependent manner. Thus, miR-1 plays an important role in the regulation of the chondrocyte phenotype during the growth plate development via direct targeting of HDAC4. — Li, P., Wei, X., Guan, Y., Chen, Q., Zhao, T., Sun, C., Wei, L. MicroRNA-1 regulates chondrocyte phenotype by repressing histone deacetylase 4 during growth plate development.